Designing and Modeling of a Dual-Band High-Efficiency Rectenna Using Dielectric Resonant Antenna Array - Jianxing Li; Ziyue Li; Cheng Jiang; Tong Wei; Zan Liu (Applied Sciences, 2022)
In this paper, we proposed a high-efficiency 2.45 GHz and 5.8 GHz dual-band rectenna for wireless energy harvesting (WEH). First, a dual-band dielectric resonant antenna (DRA) was designed. A 4-element DRA array was further developed using a compact feeding network. The measured gains of the DRA array were 5.5 dBi at 2.45 GHz and 12.9 dBi at 5.8 GHz. Then, a new type of impedance regulation stub (IRS) was introduced that significantly improved the conversion efficiency of the rectenna. The result showed that the conversion efficiency of the rectifier was 66% and 62% at 2.45 GHz and 5.8 GHz, respectively, when the input power level was 10 dBm. Furthermore, the proposed rectenna was validated to activate a standard BQ25504 DC-to-DC boost converter and charge a supercapacitor. The results demonstrated that the proposed rectenna could be an appropriate solution for WEH applications.